2015
DOI: 10.1111/brv.12230
|View full text |Cite
|
Sign up to set email alerts
|

Colour spaces in ecology and evolutionary biology

Abstract: The recognition that animals sense the world in a different way than we do has unlocked important lines of research in ecology and evolutionary biology. In practice, the subjective study of natural stimuli has been permitted by perceptual spaces, which are graphical models of how stimuli are perceived by a given animal. Because colour vision is arguably the best-known sensory modality in most animals, a diversity of colour spaces are now available to visual ecologists, ranging from generalist and basic models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 175 publications
(255 reference statements)
0
172
1
1
Order By: Relevance
“…Is a color patch differing by 5 JNDs as discriminable from a reference as a patch differing by 7 JNDs? Following Fechner’s assumption of additivity, large colorspace should be possible to model (discussed in [95, 96] among others). Furthermore, the only study investigating a behavioral response (in this case the visual attention reflex) in relation to perceptually large color distances found that just-noticeable-differences, as calculated by the receptor noise model, are effective in describing colors separated by large distances in visual space [97].…”
Section: Discussionmentioning
confidence: 99%
“…Is a color patch differing by 5 JNDs as discriminable from a reference as a patch differing by 7 JNDs? Following Fechner’s assumption of additivity, large colorspace should be possible to model (discussed in [95, 96] among others). Furthermore, the only study investigating a behavioral response (in this case the visual attention reflex) in relation to perceptually large color distances found that just-noticeable-differences, as calculated by the receptor noise model, are effective in describing colors separated by large distances in visual space [97].…”
Section: Discussionmentioning
confidence: 99%
“…We trained chickens to discriminate a rewarded orange (S+) from an unrewarded yellow (S2) in the control illumination (Renoult et al, 2015;. (C) Chromaticity diagram (VS, S, M and L indicate violet-, shortwavelength-, medium-wavelength-and longwavelength-sensitive cone types, respectively) of all stimuli in experiment 1, using the RNL model, for adaptation to the grey background under white illumination (grey circle).…”
Section: Methodsmentioning
confidence: 99%
“…In other animal species, the psychological color space has only been investigated, via discrimination tasks, for a limited number of species (Renoult et al, 2015). However, the dimensionality of the space varies from one-dimensional (black-white) two-dimensional (in most mammals), three-dimensional (e.g., in primates), to four-dimensional (in some birds and fish).…”
Section: Basic Psychological Spacesmentioning
confidence: 99%
“…A paradigmatic example is the color space (Vos, 2006; Renoult et al, 2015), but also, for example, the emotion space (Russell, 1980; Mehrabian, 1996) and musical space (Longuet-Higgins, 1976; Shepard, 1982; Large, 2010) have been extensively studied. Within cognitive linguistics, such spaces are also assumed to be carriers of meaning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation